Review of Evanthis Hatzivassiliou's, NATO and Western Perceptions of the Soviet Bloc: Alliance Analysis and Reporting, 1951-1969 - Roussos, Sotiris (Historein, 2016)
Evanthis Hatzivassiliou. NATO and Western Perceptions of the Soviet Bloc: Alliance Analysis and Reporting, 1951-1969. London: Routledge, 2014. xii + 228 pp.